REVIEW OF INSULIN THERAPY - Ahlam salih sahel alenazi; Asmaa Abdulleh Alenazi; Noura Attallah Alonaze; Sheemah bakeet alonazi; Wafa bakeet alonazi; Nawal bakeet alonazi; Aladham hamdan alanazi; Amal Mohammed alanizi; Yousef miqed Alharbi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The objective of this article is to review the different types of insulin and to explain some of the different dosing regimens that are used. Articles were obtained via a MEDLINE search and product package inserts. There is no one insulin therapy that is best for all patients. Type 1 diabetes patients require insulin therapy to maintain life. Studies support intensive in-sulin dosing in these patients to obtain an A1C of less than 7.0%. Insulin therapy for type 2 diabetes patients may be a little less clear. Long-acting insulin in combination with an oral agent may be just as effective as insulin alone, and in pa- tients who fail oral therapy, a simple insulin regimen is preferred over a complex one.